Temporal dynamics of neutrophil functions in multiple sclerosis - Shishi Shen; Shilin Wu; Yuge Wang; Li Xiao; Xiaobo Sun; Wenxuan Sun; Yipeng Zhao; Rui Li; Jiaqi Zhang; Zhanhang Wang; Shaoli Zhou; Shixiong Huang; et al. (Neurobiology of Disease)
Early neuroinflammatory injury plays a crucial role in initiating and progressing multiple sclerosis (MS). Neutrophils are forerunners to neural lesions in MS, yet the temporal alterations of their functions in MS remains unclear. This study demonstrated a positive correlation between circulatory neutrophil counts and disease activity and severity in treatment-naïve MS patients. In experimental autoimmune encephalomyelitis (EAE), we documented the recruitment of neutrophils to spinal cord during the preclinical phase, with these cells contributing to the disruption of the blood-spinal cord barrier (BSCB) during the onset of the disease. Furthermore, during the peak phase, infiltrated neutrophils promoted demyelination through formation of neutrophil extracellular traps (NETs), cytokine secretion and antigen presentation. Notably, the inhibition of neutrophil infiltration using a CXCR2 inhibitor effectively mitigated white matter damage and physical disability, underscoring their potential as therapeutic targets. In conclusion, neutrophils represent promising candidates for both disease treatment and prognosis evaluation in MS. By elucidating their temporal roles and mechanisms of action, we can potentially harness their modulation to improve patient outcomes and disease management.